2011
DOI: 10.1016/j.ajpath.2011.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Lack of TNF-α–Induced MMP-9 Production and Abnormal E-Cadherin Redistribution Associated with Compromised Fusion in MCP-1–Null Macrophages

Abstract: Homotypic cell fusion occurs in several cell types including macrophages in the formation of foreign body giant cells. Previously, monocyte chemoattractant protein-1 (MCP-1) was demonstrated to be required for foreign body giant cell formation in the foreign body response. The present study investigated the fusion defect in MCP-1-null macrophages by implanting biomaterials intraperitoneally in wildtype and MCP-1-null mice and monitoring the macrophage response at 12 hours to 4 weeks. MCP-1-null mice exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 47 publications
4
72
0
2
Order By: Relevance
“…Cadherins help to maintain blood vessel integrity (5). MMP-9 has been reported to downregulate cadherins through proteolytic shedding, which would increase vascular permeability (9,32). The absence of a similar increase of Cdh1 in the Null mice suggests that the increase in the WT may be a compensatory mechanism to improve impaired vascular permeability.…”
Section: Discussionmentioning
confidence: 86%
“…Cadherins help to maintain blood vessel integrity (5). MMP-9 has been reported to downregulate cadherins through proteolytic shedding, which would increase vascular permeability (9,32). The absence of a similar increase of Cdh1 in the Null mice suggests that the increase in the WT may be a compensatory mechanism to improve impaired vascular permeability.…”
Section: Discussionmentioning
confidence: 86%
“…Compared with control macrophages, β-catenin-deficient macrophages showed decreased expression of numerous genes with functions attributed to migration and adhesion, including members of the cadherin, integrin, and a disintegrin and metalloproteinase (ADAM) gene families (Gene Expression Omnibus database, GEO GSE52163) (Supplemental Table 2). Cadherins and catenins are important for macrophage cell contact (27)(28)(29)(30)(31), whereas ADAMs and integrins are important for macrophage cell migration (32). More than 50% of ADAM and integrin gene family members showed lower expression levels in macrophages from Lysz-Cre Catnb tm2KEM mice compared with those observed in control macrophages (Supplemental Table 3 and Supplemental Table 4).…”
Section: Lysozyme-expressing Progeny Cells Account For 18% Of Cells Imentioning
confidence: 98%
“…For example, fusion of macrophages results in the formation of multinucleated giant cells (MNGs), which is a typical feature of granulomatous inflammation and foreign body reactions. [94][95][96][97][98] Moreno et al found that IL-4 induces MNG generation in a STAT6-dependent manner by regulating the expression of at least 2 fusion mediators, E-cadherin and DC-STAMP, resulting in homotypic macrophage fusion and engulfment of large foreign bodies. 99 In addition TREM-2 and its signaling association partner DAP12 are required for IL-4-induced E-cadherin and DC-STAMP expression, and giant cell formation in vitro and in vivo.…”
Section: E-cadherin Contributes To Macrophage Fusion and Osteoclastogmentioning
confidence: 99%